Experimental study of heat transfer to non-Newtonian fluids inside a scraped surface heat exchanger using a generalization method. (March 2018) - Crespí-Llorens, D.; Vicente, P.; Viedma, A.
Highlights: The performance of a scraped surface enhanced heat exchanger has been evaluated. A non-dimensional analysis of pressure drop and heat transfer has been performed. Pseudoplasticity effects on pressure drop and heat transfer have been quantified. The use of a viscosity generalization method for this device has been found valid. Abstract: The heat transfer process to a non-Newtonian pseudoplastic fluid inside a scraped surface heat exchanger has been experimentally analysed. The scraping device consists of a rod with semicircular pieces mounted on it, which are in contact with the inner surface of the pipe. The whole moves axially and thus, the pieces scrape the inner surface of the pipe, in order to avoid fouling formation and enhance heat transfer. Pressure drop, heat transfer and power consumption measurements, using non-Newtonian pseudoplastic fluids, have been carried out in static and dynamic conditions of the scraper. Four flow regions have been identified: attached laminar, detached laminar, transitional and turbulent flow regions. A generalization method for the fluid viscosity that includes the effects of the non-Newtonian behaviour has been used. Friction factor and Nusselt number have been successfully correlated by employing the generalized viscosity on pressure drop and heat transfer results, both in static and dynamic conditions, for three of the four identified flow regions (it was not possible to get correlations in the transition to turbulent flow region). The study shows that, despite the high power consumption of the scraping movement, the device is suitable for an industrial process using non-Newtonian fluids, since it prevents fouling, increases heat transfer, provides flexibility and enhances the final product quality. Furthermore, the obtained correlations are a valuable tool in the design of heat exchangers.